Photocatalytic activity of cu-doped cerium dioxide nanoparticles - Channei D. (2017)
© 2017 Trans Tech Publications, Switzerland. Pure CeO2 and Cu-doped CeO2 nanoparticles with different doping amounts of Cu in the range of 0.5-2.0 wt.% were synthesized by the combination of homogeneous precipitation and impregnation methods. The effect of Cu on the correlation of structural, optical and photocatalytic properties of CeO2 were studied. The XRD results indicated that phase structures of pure CeO2 and Cu-doped CeO2 nanoparticles were cubic fluorite phase and no other characteristic peaks related to Cu were detected. TEM images revealed that all samples were spherical in shape with the size less than 10 nm. The shift of absorption edge of Cu-doped CeO2 catalysts, corresponding to a decrease of band gap energies from 3.2 to 2.8 eV, was also observed as the amount of Cu dopant increased. The photocatalytic performances of the Cu-doped CeO2 exhibited higher activity than pure CeO2 for photocatalytic degradation of methylene blue under visible light irradiation, and the CeO2 doped with 1.0 wt.% Cu exhibited the highest photocatalytic activity.